Follow-up of children and adolescents with short stature: the importance of the growth rate - Strufaldi, Maria Wany louzada; Silva, Edina Mariko Koga da; Puccini, Rosana Fiorini (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Short stature is delined m a height oi more than two standard deviations below the average for a given age and sex in a reference population. The objeclive was to describe lollow-up conducted among shorl-slalure children and adolescenls. DESIGN AND SETTING: Descriptive study, ai lhe Growth outpatient clin ic, Department oi Pediatrics, Universidade Federal de São Paulo. METHODS: lhe study included 15 2 patients aged 2 to 15 years who had height for age oi less than P5, on the National Center for Health Statistics curve. The children underwent nutritional evaluation, and several variables relating to height and growth rate were calculated to establish etiological diagnosis. Bone age was evaluated by X-ray. RESULTS: lhe majority (63.2%) were male. ln 77.8%, lhe slalure observed was within lhe lamily pattern. Among the 99 patients followed up for more than 6 months, 17.2% presented inadequate growth rates. lhe preponderant etiological diagnosis for short stature was lamilial/constitutional in 58.6% oi the cases; 27 patients (34.2%) with adequate growth rate presented bone age alterations. Even with inadequate growth rates, 75% oi such patients had a normal result lrom growth hormone stimulation testing. Close to 90% oi patients with a d iagnosis oi short stature oi familial/constitutional origin and inlraulerine growth retardation presented adequate growth rate. The genetic etiology was signilicantly characlerislic oi palienls with inadequate growth rate. CONCLUSION: Growth rate assessment must form part oi the investigation and lollow-up oi short-stature cases. However, its utilization and validity should form pari oi an overall view oi each patient.